HUBUNGAN KADAR ZINK SERUM DENGAN DERAJAT NEUROPATI DIABETIK - Udi Panata,* Dodik Tugasworo,* Amin Husni* (Neurona Majalah Kedokteran Neuro Sains, 2019)
INTRODUCTION DIABETIC NEUROPATHY DN IS ONE OF THE COMPLICATIONS IN DIABETES MELLITUS DM THAT OCCURS FREQUENTLY THIS MIGHT BE CAUSED BY DEFICIENCIES OF TRACE ELEMENTS SUCH AS ZINC RELATED TO THE COMPLICATIONS ZINC CONTROLS HYPERGLYCEMIC FACTOR AND OXIDATIVE STRESS CAUSED BY HYPERGLYCEMIA WHICH CAUSES DN